PERANCANGAN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) HYBRID MENGGUNAKAN AUTOMATIC TRANSFER SWITCH DI PROKLAMATOR KOI, BLITAR - Alfian Pramudika Sugiyanto; Hadi Suyono; n/a Nurussa’adah (Jurnal Mahasiswa TEUB, 2023)
Solar energy is a renewable energy source, which can be used to produce electricity. The problem experienced at the locations of Proklamator Koi partners is that there are frequent power outages because they are located in rural areas that have poor electrical reliability, so the design of the Hybrid PLTS system was carried out as a solution to this problem. The purpose of designing this tool is to create a Hybrid PLTS system that is capable of producing an alternative source of electrical energy from solar panels as a backup power source. This system uses the main components of solar panels with a total capacity of 200WP, 30A Solar Charge Controller, 1000W Inverter and Automatic Transfer Switch. From the test results, it was found that the maximum output power produced by the 200WP solar panel is 151.33W. The electric power supply from the PLTS is capable of charging a12V 100Ah battery for approximately 8 hours from a 12V battery condition to 13.6V and can be used as a 48W water pump power supply for approximately 10 hours 30 minutes from 13.3V battery condition to battery reaches 12V or 50% battery capacity. The average inverter output voltage is 228.28V and the average ATS switching time in transferring the power source from PLN to inverter takes 0.288s and from inverter to PLN takes 0.151s. Then, the initial capital spent in designing this Hybrid PLTS system was IDR 5,688,500.00 with operational and maintenance costs of IDR 113,770.00 a year. Keywords: Water Pumps, Koi Fish Cultivation, Hybrid PLTS, Automatic Transfer Switch.